DNA methylation profiling of non-small cell lung cancer reveals a COPD-driven immune-related signature. Issue 12 (8th September 2015) - Wauters, Els; Janssens, Wim; Vansteenkiste, Johan; Decaluwé, Herbert; Heulens, Nele; Thienpont, Bernard; Zhao, Hui; Smeets, Dominiek; Sagaert, Xavier; Coolen, Johan; Decramer, Marc; Liston, Adrian; et al.
Abstract : Introduction: Non-small cell lung cancer (NSCLC) is a heterogeneous disorder consisting of distinct molecular subtypes each characterised by specific genetic and epigenetic profiles. Here, we aimed to identify novel NSCLC subtypes based on genome-wide methylation data, assess their relationship with smoking behaviour, age, COPD, emphysema and tumour histopathology, and identify the molecular pathways underlying each subtype. Methods: Methylation profiling was performed on 49 pairs of tumour and adjacent lung tissue using Illumina 450 K arrays. Transcriptome sequencing was performed using Illumina HiSeq2000 and validated using expression data from The Cancer Genome Atlas (TCGA). Tumour immune cell infiltration was investigated by immunohistochemistry. Results: Unsupervised hierarchical clustering of tumour methylation data revealed two subgroups characterised by a significant association between cluster membership and presence of COPD (p=0.024). Ontology analysis of genes containing differentially methylated CpGs (false discovery rate, FDR-adjusted p<0.05) revealed that immune genes were strongly enriched in COPD tumours, but not in non-COPD tumours. This COPD-specific immune signature was attributable to methylation changes in immune genes expressed either by tumour cells or tumour-infiltrating immune cells. No such differences were observed in adjacent tissue. Transcriptome profiling similarly revealed that genes involved in the immune response were differentially expressed in COPD tumours (FDR-adjusted p<0.05), an observation that was independently replicated using TCGA data. Immunohistochemistry validated these findings, revealing fewer CD4-positive T lymphocytes in tumours derived from patients with COPD. Conclusions: Lung tumours of patients with COPD differ from those of patients without COPD, with differentially methylated and expressed genes being mainly involved in the immune response.